LEGALITAS FOTO C1 PLANO PENGAWAS TPS PADA REKAPITULASI PENGHITUNGAN PEROLEHAN SUARA DI TINGKAT KECAMATAN DALAM PEMILIHAN UMUM DI KABUPATEN SEMARANG - Maskup Asyadi; Putri Hergianasari; Roberto Octavianus Cornelis Seba (KRITIS, 2023)
The application of the legality principle to the C1 Plano photo of the Voting Place Supervisor as a basis when matching the difference in the vote count in the sub-districts is something that should be considered. This study uses a qualitative method with purposive sampling, namely in PPK Semarang Regency. In carrying out the recapitulation in one of the sub-districts in Semarang Regency, there was a District Election Supervisory Committee recommendation step which made the C1 Plano photo documentation from PTPS as the basis for correcting the C1 Hologram data which was different between the one in the box and the copy of C1 owned by the witness. Article 22 paragraph (2) of PKPU 4 of 2019 clearly explains if there is a difference in the recapitulation of the results of the vote to match it with C1 Plano. The meaning of C1 Plano by some District Election Supervisory Committee is compared to the Photo of C1 Plano obtained from the Voting Place Supervisor, in addition to the reason to speed up the recapitulation process, considering that C1 Plano is contained in a box according to the type of election, which is not located in the same place as the location of the recapitulation. The District Election Committee as a form of obedience to the principle of legality continues to take C1 Plano in the box as a manifestation of the implementation of elections with integrity. However, in one sub-district there was a difference of perception regarding this matter, which resulted in PPK being asked not to take C1 Plano, just based on the photo of C1 Plano owned by District Election Supervisory Committee. This is where the need for the application of the principle of legality to provide legal certainty for the implementation of the recapitulation stage in the 2019 Election.